2015
DOI: 10.1590/0103-8478cr20141428
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the abortion risk difference in Neospora caninum seropositive dairy cattle in Brazil

Abstract: <p>Neosporosis in cattle herds is associated with large economic losses, with abortion being the only clinical sign perceptible to the producer. Losses are estimated at over one billion dollars worldwide. This study aimed to estimate the abortion risk difference in seropositive animals using specific data for dairy herds in Brazil. Differences in the risk of abortion between seropositive and seronegative animals were calculated through a meta-analysis of previous data from several Brazilian states, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The rate of abortion due to N. caninum infection in dairy cows in Brazil is estimated at 10.04%, corresponding to more than 474,000 abortions per year and resulting in severe economic losses to the dairy industry (NICOLINO et al, 2015). Dubey et al (1997) reported that the detection of anti-N. caninum antibodies in the sera of cows with a history of abortion was evidence of maternal exposure to the protozoan.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of abortion due to N. caninum infection in dairy cows in Brazil is estimated at 10.04%, corresponding to more than 474,000 abortions per year and resulting in severe economic losses to the dairy industry (NICOLINO et al, 2015). Dubey et al (1997) reported that the detection of anti-N. caninum antibodies in the sera of cows with a history of abortion was evidence of maternal exposure to the protozoan.…”
Section: Resultsmentioning
confidence: 99%
“…Approximately two-thirds of this total (USD 1.58 billion) is related to production losses in dairy cattle (REICHEL et al, 2013). Reichel et al (2013) and Nicolino et al (2015) estimated the costs related to N. caninum infections in Brazil at R$ 291 million and USD 51.3 million, respectively. Therefore, losses due to neosporosis account for approximately 1% of the gross value of dairy production in Brazil, which has high socioeconomic importance.…”
Section: Introductionmentioning
confidence: 99%
“…For example in South America the annual losses due to Neosporosis for the dairy industry were estimated to be $43. 6 [10,11] In addition to economic losses, some livestock abortigenic agents are zoonotic making them relevant to human health as well. Some of those infectious agents, including Brucella abortus, Rift valley fever, Toxoplasma gondii and Campylobacter among others, can cause fever and abortion in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Mundialmente, a neosporose representa uma das principais causas de aborto parasitário em bovinos, sendo responsável por surtos em série em rebanhos. A infecção por N. caninum é altamente prevalente no Brasil e estima-se que essa doença aumenta em 10% o risco de aborto em rebanhos leiteiros em nosso país, gerando altos custos para os produtores (NICOLINO et al, 2015;CERQUEIRA-CÉZAR et al, 2017). Além disso, o prejuízo global causado pela neosporose é avaliado em bilhões de dólares (REICHEL et al, 2013).…”
Section: Justificativa E Relação Entre Os Capítulos Da Teseunclassified